ТИББИЁТ ОЛИЙ ЎҚУВ ЮРТЛАРИДА КИМЁ ФАНИНИ ЎҚИТИШ ЖАРАЁНИНИ CLIL УСУЛИ ЁРДАМИДА ТАШКИЛЛАШТИРИШ - Сафарова, Н.С. (SCIENCE and SOCIETY, 2020)
The article describes the CLIL method, which has recently been introduced into the practice of teaching integrated with the English language in our country. Its importance is revealed by the example of the process of chemistry education in national groups in the direction "Pharmacy" at the Bukhara Medical Institute. Concrete proposals and conclusions are made for each stage of the integrated process of language and natural science education.
Keywords: CLIL method; stages of the lesson based on integration of science and language; glossary of scientific terms; organization of the learning process based on CLIL method; role of the teacher in the learning process